Efficacy of Co-Adjuvant Melatonin and Resveratrol Chronotherapy for Pregnancy Achievement in Premature Ovarian Failure (POF) - Pagano, Eleonora Samanta (2023)
Premature Ovarian Failure/Insufficiency (POF/POI) is a severe chronic female condition characterized by low peripheral E2 and FSH levels before 40 years age. Available therapy did not demonstrate any significant improvement in fertility rate, delaying menopausal symptomatology, and long-term E2 deprivation effects. To restore normal reproductive function, general health and well-being, we proposed to treat POF women with physiological Hormone Replacement Therapy (pHRT), plus Melatonin (MEL) and Resveratrol (RESV). A 39-year-old POF woman, diagnosed after meeting hormonal criteria, emotional distress, miscarriages, and history of familial early menopause and autoimmune disease, poorly tolerated oral contraceptive HRT. Later on, started on natural E2 and micronized Progesterone (P4) treatment; however, no amelioration was achieved. We then started with a "physiological-like¨ schedule, consisting in mimicking a normal female cycle; i.e., hormone doses and timing profile similar to the natural cycle. Because patient was thin, the lowest E2 dose to obtain physiological E2 levels was chosen. After a 3 month-pHRT combined with MEL (50 mg/night) and RESV (100 mg/day) administration, peripheral hormone levels reached not only physiological values but also comparable to those seen on fertile stage, as well as a corresponding cervical mucus pattern and reported sense of “well-being". Five months later, peripheral hCG and abdominal ultrasound confirmed spontaneous pregnancy, on time a healthy baby was born at term by natural delivery. Thus, pHRT and adjusted endogenous rhythm, due to MEL+RESV, could result in novel and multiple health women’s benefits. Therefore pHRT+MEL+RESV therapy should be strongly considered for treating POF/POI and perimenopausal women.